Cellular interactions with biodegradable polyurethanes formulated from L-tyrosine. (May 2013) - Shah, Parth N; Yun, Yang H
L-Tyrosine polyurethanes (LTUs) have been synthesized by structural modification of the poly (amino acid) backbone to circumvent the problems associated with the processing of poly (amino acids) arising from their high crystallinity, insolubility in common organic solvents, and high glass-transition and melting temperatures. Additionally, problems such as unpredictable swelling characteristics, change in conformation, and uncontrolled enzymatic degradation have severely restricted the use of poly (amino acids). In contrast, LTUs are designed to retain their superior physico-chemical properties, while incorporating biodegradability through enzymatic, hydrolytic, and oxidative pathways. The aim of this study is to evaluate initially the biocompatibility of LTUs and their degradation products. Studies involving primary dermal human fibroblasts cultured in contact with LTU films or degradation products suggest a lack of toxicity (cell viabilities >93% with p  < 0.05 compared to the control for all studies). The diversity of LTU polymer chemistry and the ability of LTUs to phase separate seem to present a heterogeneous surface with variable wettability. This phenomenon influences the adhesion and proliferation of human fibroblasts on polymeric surfaces, wherein fibroblast adhesion on polycaprolactone diol (PCL) based LTUs is characterized by higher cell counts (81, 250 ± 18, 390 for PCL-C-DTH (desaminotyrosine–tyrosyl hexyl, DTH), 58, 360 ± 7370 for PCL-L-DTH, 38, 480 ± 12, 680 for PEG-C-DTH (polyethylene glycol, PEG), and 46, 430 ± 16, 000 for PEG-L-DTH at 120 h with p  < 0.001 for comparison between PCL-C-DTH and all other LTUs), more rapid cellular proliferation (doubling time of 37–49 h for PCL-based LTUs compared to 68–90 h for PEG-based LTUs), and a uniform cell distribution compared to PEG-based LTUs. However, immunofluorescence assay for F-actin suggests that the cells are well attached. Thus, the lack of cytotoxicity and the ability to control cellular adhesion through polymer chemistry make LTUs attractive candidates for tissue-engineering applications that require elastomeric, biodegradable, and biocompatible polymers.